A Study on Depression among Transgender Residing In Chennai District, Tamil Nadu - Krishna Prasanth B; Mahalakshmi K; Umadevi R; Anandhaeashwar VM (Medsci Publications, 2022)
Introduction: In India, transgender population is one among the stigmatized and discriminated sector who face a lot of psychological problems due to their gender identity and lack of support. The study was done with the major objective to find out the prevalence of depression and the associated factors among transgender people residing in Chennai district. Methodology: This is a descriptive cross-sectional study done among 178 transgender residing in Chennai district selected by snowball sampling method. Patient Health Questionnaire - 9 was used to assess the prevalence of depression and semi-structured questionnaire was used to collect details regarding associated factors. Data was analyzed using SPSS version 22. Results: The prevalence of depression among the present study was found out to be 76.8%. The major factors associated with depression were found to be lack of family and social support, faced violence due to discrimination and involvement is sex work which had a statistically significant association. Conclusion: Outreach camps have to be conducted among transgender population to screen for common mental health problems like depression and provide counseling to them and identify their problems and measures can be taken to address the same.